IMPLEMENTASI KEBIJAKAN AFIRMATIVE ACTION PADA BADAN PENGAWAS PEMILU PROVINSI JAWA BARAT - Wulandari, Rafih Sri (Bawaslu Provinsi Jawa Barat, 2023)
Affirmative Action Policies passed and set by political decision makers to pay attention to the optimization of Affirmative groups in politics, especially election organizers as stated in the Law. No. 17 of 2017.This law has a very important role to show the government's special attention in responding to the emerging issues of Gender, people with disabilities, indigenous peoples. This implementation is relatively difficult to carry out due to the many challenges faced by the relevant parties. The policy implementation model conceptually seeks to make it easier for policy analysts, policy implementers, policy objectives and stakeholders to be able to measure the success of this policy running appropriately. The implementation of this Law is the obligation and full attention of the central/regional government and related parties, in this case, election organizers to be able to answer and realize this Affirmative Action on target according to regulations set in the West Java Province.